Innovation of Local Wisdom Based Pop-Up Book Learning Media to Foster Students’ Character Development - Alphonsus Ulung Tegar Oktovian; Dionisius Heckie Puspoko Jati; Nani Mediatati; Rebeka Sri Minati (Lembaran Ilmu Kependidikan, 2026)
Background –The  background of this research is  based  on the  perception  that learning geometry at the elementary  school  level  is  often  considered  monotonous  and  less  interesting,  due  to  the  lack  of  varied teaching methods and the lack of material connection with students' daily lives. Purpose –To increase students' interest in learning, creativity, and understanding, this research integrates the traditional Mountain Tread gamewith the concept of Fibonacci. Method/Approach–With   a   qualitative   approach,   data   collection   was   done   through   observation, interviews, and documentation during the learning process. Findings –The results showed that the use of this media was able to improve students' understanding of geometric  shapes  and  patterns,  while  stimulating  their  creativity  in  forming  and  exploring  geometric patterns based on the Fibonacci concept. Conclusions–In conclusion, combining traditional games and the Fibonacci concept is an effective strategy in developing creativity and understanding of geometry at the elementary school level, with the advantage of keeping up with the times while preserving local culture. Novelty/Originality/Value - This study offers an innovative integration of local wisdom content with three-dimensional Pop-Up Book design as a character education tool.